2003
DOI: 10.1111/j.1471-0366.2004.00072.x
|View full text |Cite
|
Sign up to set email alerts
|

Redistributive Land Reform: No April Rose. The Poverty of Berry and Cline and GKI on the Inverse Relationship

Abstract: At the theoretical heart of the Griffin, Khan and Ickowitz (GKI) case for redistributive land reform (‘a many‐splendoured thing’) lies the highly influential study by Albert Berry and William Cline, Agrarian Structure and Productivity in Developing Countries, published for the ILO in 1979. That study is regarded by many as the definitive work on the inverse relationship between farm size and land productivity. This paper subjects Berry and Cline, and by extension GKI, to critical scrutiny with respect to their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 18 publications
0
26
0
4
Order By: Relevance
“…For example, Griffin et al (2004: 371) note the U-shaped findings in the study of centre-west Brazil mentioned by Dyer (2004), but they also report on a study of north-east Brazil that found a clear inverse relationship after controlling for soil conditions. Using dummies for the type of production undertaken (to control for land quality differences), Deininger et al (2003Deininger et al ( : 1395 find a large and statistically important negative relationship between farm profits per acre and size in Nicaragua.…”
Section: The Empirical Findings In the Size -Efficiency Debatementioning
confidence: 91%
See 2 more Smart Citations
“…For example, Griffin et al (2004: 371) note the U-shaped findings in the study of centre-west Brazil mentioned by Dyer (2004), but they also report on a study of north-east Brazil that found a clear inverse relationship after controlling for soil conditions. Using dummies for the type of production undertaken (to control for land quality differences), Deininger et al (2003Deininger et al ( : 1395 find a large and statistically important negative relationship between farm profits per acre and size in Nicaragua.…”
Section: The Empirical Findings In the Size -Efficiency Debatementioning
confidence: 91%
“…However, Dyer (2004) has made a damaging methodological critique of these two studies. He argues that a crucial distinction must be made between aggregated levels of analysis (for countries or regions) and disaggregated studies.…”
Section: The Empirical Findings In the Size -Efficiency Debatementioning
confidence: 95%
See 1 more Smart Citation
“…One the one hand, advocates of small-scale production units argue that small farms are more labourintensive and hence more 'efficient', producing greater yield per unit area as well as greater employment (Lipton 1977, Griffin et al 2002. On the other hand, critics argue higher land productivity on smaller farms may be illusory, reflecting denser population in more fertile areas (Dyer 2004), or that it arises not from greater efficiency, but from greater selfexploitation, of family labour (Byres 2004). This latter point is illustrated by a World Bank study comparing production costs in Brazil, Thailand and four African countries, which observed:…”
Section: Investment Productivity and The Water Constraint In Africanmentioning
confidence: 99%
“…Therefore, disentangling the possible causes of variation, we find that the impact of land distribution from large/rich to small/poor landowners has no predefined effect on growth per se, but depends on the relative importance of other economic factors present in each specific location. In fact, we can find new empirical evidence on the size-productivity relationship in developing countries showing all the different relationships that one can imagine (see, for example, Dyer, 2004). The conclusion is straightforward: the need to distribute land when ownership is skewed cannot be universally justified from a microeconomic analysis perspective.…”
mentioning
confidence: 91%